Behavioural and physical signs associated with oestrus and some aspects of reproductive performance in Fogera cows and heifers - Negussie, F.; Kassa, T.; Tibbo, Markos (Springer, 2002)
An investigation was carried out into the behavioural and physical signs of oestrus in 70 Fogera cows and heifers between December 1993 and May 1994 at Metekel Cattle Breeding and Improvement Ranch, Ethiopia. Retrospective information generated from records made between 1991 and 1994 was evaluated for some aspects of the reproductive indices. The mean±SD duration of oestrus (n = 136) was 10.6±4.5 h (range 2.2–21). Most oestruses (63.2%) started during the day (06:00–18:00). The incidence of oestrus was significantly affected by months (?2 = 21.86; p<0.001). Among the physical signs, standing to be mounted was the most consistent indication (97.8%) of oestrus. About 12.5% of the cows in oestrus did not mount other cows. The retrospective study indicated that the mean inter-oestrus interval for 46 oestruses was 29.2±19.7 days. The average gestation length for 141 cows was 276 days. Continuous and careful observation of oestrus would reduce the reproductive wastage that arises from less pronounced heat periods and those occurring at night, especially for ranches that use artificial insemination and have a limited number of bulls.